2022
DOI: 10.3389/fpls.2022.1035549
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic and plant growth promotion of rhizobacteria against Phytophthora colocasiae in taro

Abstract: Taro leaf blight caused by Phytophthora colocasiae adversely affects the growth and yield of taro. The management of this disease depends heavily on synthetic fungicides. These compounds, however, pose potential hazards to human health and the environment. The present study aimed to investigate an alternative approach for plant growth promotion and disease control by evaluating seven different bacterial strains (viz., Serratia plymuthica, S412; S. plymuthica, S414; S. plymuthica, AS13; S. proteamaculans, S4; S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 94 publications
0
6
0
Order By: Relevance
“…The activation of auxin biosynthesis genes and production of IAA by SLU99 ( Kelbessa et al., 2022 ) prompted us to analyze the differences in the expression of genes involved in auxin signaling pathways. Major auxin-responsive genes such as Gretchen Hagen 3 ( GH3 ) and small auxin up RNA ( SAUR ) are transcriptionally regulated by auxin at early stages of signal transduction.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The activation of auxin biosynthesis genes and production of IAA by SLU99 ( Kelbessa et al., 2022 ) prompted us to analyze the differences in the expression of genes involved in auxin signaling pathways. Major auxin-responsive genes such as Gretchen Hagen 3 ( GH3 ) and small auxin up RNA ( SAUR ) are transcriptionally regulated by auxin at early stages of signal transduction.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research found that bacterial consortiums aid plant growth by enhancing stress tolerance ( Silambarasan et al., 2019 ; Yang et al., 2021 ; Kelbessa et al., 2023 ). Recently, results from our group demonstrated that SLU99 is compatible with strains EV23 and AV10 ( Kelbessa et al., 2022 ), implying that these bacteria could co-exist as a consortium in the rhizosphere. Considering that all these strains are potent biocontrol agents ( Kelbessa et al., 2022 ), a bacterial consortium of these strains could act synergistically to contribute to reducing disease under natural conditions.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The strains used in this study were isolated from potato and tomato rhizosphere soils. In vitro antagonistic analysis indicated a strong antagonistic activity against plant pathogens, including P. colocasiae (Kelbessa et al, 2022), P. infestans and R. solani (unpublished). The aim of this study was to conduct a holistic study on the effect of PGPR on potato and tomato growth and select the best-performing PGPR to gain insights into their mechanism of action.…”
Section: Introductionmentioning
confidence: 99%